Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Minat Beli Ulang Melalui Kepuasan Pelanggan pada Famicafe Surabaya - Henrico Priardi Atmaja; Titik Inayati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of product quality and service quality on repurchase intention through customer satisfaction at Famicafe Surabaya. The background of this research is driven by the rapid growth of the retail cafe industry in Surabaya and a recorded 23.8% decline in total transaction volume at Famicafe during the final quarter of 2025. This study employs a quantitative approach involving 100 respondents selected via purposive sampling, and data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that product quality does not have a significant direct effect on repurchase intention. However, service quality and customer satisfaction were found to have a positive and significant influence on repurchase intention. Furthermore, product quality and service quality significantly influence customer satisfaction. Crucially, customer satisfaction acts as a full mediator linking product quality to repurchase intention and as an essential mediator in the relationship between service quality and repurchase intention. These findings confirm that to foster loyalty and boost repurchase intention at Famicafe Surabaya, product and service excellence must be effectively translated into actual customer satisfaction.